Assessing the Role of Saliva and Urine in Detecting Molecular Markers of Plasmodium falciparum Resistance to Antimalarial Drugs - Dagnogo Oléfongo; Dago Dougba Noél; Kouman Kouamé Bouatini Angélo; Ako Ako Ako Aristide Bérenger; Bla Kouakou; Touré Offianan André; Djaman Allico Joseph (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
Background: Various interventions such as insecticide-treated nets, indoor residual spraying, antimalarial drugs, rapid diagnostic tests, and, more recently, vaccines (RTS, S/AS01, and R21/Matrix-M), continue to play a crucial role in the malaria control strategy. The malaria diagnostic tools developed to date require blood to be taken. However, certain groups in the population are reluctant to take and or give blood samples because of their cultural habits (blood taboo), or because of the fear associated with the trauma of the injection, especially when the sample is taken repeatedly. Saliva and urine, which are not very invasive to collect, have not been widely used for malaria diagnosis. The aim of this study is to assess the performance of saliva and urine in detecting molecular markers of Plasmodium falciparum resistance to antimalarial drugs. Methodology: This prospective study took place at the Anonkoua Kouté Health Center and the Port-Bouët and Ayamégeneral hospitals from February to August 2015. Blood, urine, and saliva samples were collected in three different localities from 94 patients over 2 years of age with microscopically confirmed Plasmodium falciparum uncomplicated malaria. P. falciparum genomic DNA (Deoxyribonucleic acid) was then extracted and amplified using primers specific for the Pfcrt (Plasmodium falciparum Chloroquine Resistance Transporter), Pfdhfr (Plasmodium falciparum dihydrofolate reductase) and PfK13 propeller (Plasmodium falciparum Kelch13 propeller) genes. The amplification products were processed by electrophoresis and analyzed against blood, saliva, and urine samples. A multivariate statistical analysis in the R programming environment was performed. A statistical difference and/or association was considered significant if the p-value < 0.05. Results: This study involved a comparative analysis of the amplification products of urine, saliva, and blood DNA extracts with a view to finding an alternative to blood sampling in the molecular diagnosis of malaria and the study of genetic markers of antimalarial drug resistance. Agarose gel electrophoresis of the amplification products of each gene detected the Pfcrt genes at 80.85% (76/94), Pfdhfr at 95.74% (90/94) and PfK13 Propeller at 98.93% (93/94) in blood. In saliva, gene detection levels were 50% (47/94), 69.14% (65/94) and 4.26% (4/94) respectively for the K13 propeller, Pfdhfr, and Pfcrt genes. Unlike the Pfcrt gene, which was not detected, 45.74% (43/94) and 38.30% (36/94) of PfK13 Propeller and pfdhfr genes respectively were detected in urine. Taking blood as the reference biological sample, statistical analysis showed that, unlike urine, saliva exhibited a detection performance for molecular markers of antimalarial drug resistance (pfcrt, pfdhfr, pfK13 propeller) close to that of blood (p < 0.05). The performance of saliva and urine was also assessed on the basis of the detection of the molecular markers pfdhfr, pfcrt, and pfK13 using ROC (Reciever Operational Characteristic) analysis. The data revealed a high sensitivity of saliva compared with urine in the detection of the pfdhfr, pfcrt, and pfK13 propeller genes. Conclusion: Current malaria diagnostic tools all require blood sampling, which is still not accepted by patients. The levels of detection of molecular markers of antimalarial drugs studied in saliva are close to those in blood. Saliva is a high-performance biological product that could potentially be used as an alternative non-invasive sample for the study of molecular markers of Plasmodium falciparum resistance to antimalarial drugs.